5-Aza-2’-deoxycytidine inhibits retinoblastoma cell by reactivating epigenetically silenced RASSF1A gene - Ru Liu; Xiao-Huan Zhang; Kun Zhang; Wei Li; Wen-Jun Wang; Di-Xian Luo; Ling Gao (International Journal of Ophthalmology, 2014)
AIM:To investigate the effect of 5-Aza-2’-deoxycytidine (5-Aza-CdR), a DNA methyltransferase (DNMT) inhibitor, on the growth and survival of the Chinese retinoblastoma (RB) cell line HXO-RB44.METHODS:The DNA methylation status of the Ras association domain family (RASSF1A) promoter in the presence of 5-Aza-CdR at different concentrations was analyzed by methylation-specific polymerase chain reaction (MSP). RASSF1A mRNA and protein levels were measured by semiquantitative RT-PCR and immunohistochemistry staining, respectively, when cells were treated with 5.0μmol/L of 5-Aza-CdR. The effect of 5.0μmol/L 5-Aza-CdR on the proliferation and viability of HXO-RB44 cells was examined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and flow cytometry.RESULTS:5-Aza-CdR efficiently induced cell cycle arrest at G0/G1 and apoptotic death in HXO-RB44 cells. MSP analysis showed that unmethylated RASSF1A DNA increased and methylated RASSF1A decreased in a dose-dependent manner in a range of 0.5-5.0μmol/L 5-Aza-CdR. Accordingly, RASSF1A expression was reactivated at both mRNA and protein levels. Incubation time of 5-Aza-CdR treatment also functioned as a factor for the demethylation status of RASSF1A promoter DNA, with a plateau on day four. 5-Aza-CdR at 5.0μmol/L completely demethylated the RASSF1A promoter in HXO-RB44 cells on day four, and as a result, RASSF1A expression increased significantly from day 4 to day 7.CONCLUSION: 5-Aza-CdR inhibits the growth of the HXO-RB44 RB cell line and induces apoptosis by demethylating the RASSF1A gene.